Antibacterial agent, antibacterial thermoplastic resin composite material and preparation method thereof

By using Ag2S/TiO2/lithium soapite powder antibacterial agent in thermoplastic resin composites, the problem of insufficient antibacterial performance of thermoplastic resin composites is solved, excellent physical and antibacterial properties are achieved, and its application fields are expanded.

CN119699361APending Publication Date: 2025-03-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311269946.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The application of thermoplastic resin composites in some specific fields is limited by the problem of insufficient antibacterial properties.

Method used

Ag2S/TiO2/lithium saponite powder is used as antibacterial agent, and it is crushed and sieved by lithium saponite and reacted with tetrabutyl titanate, acetone, and deionized water. Then, silver ions, thiourea and other components are added, and antibacterial agent is obtained after reaction, filtration, washing and vacuum drying, and mixed with thermoplastic resin, antioxidant and other components in a certain proportion. Through the twin screw extrusion mechanism, it is formed into an antibacterial thermoplastic resin composite material.

Benefits of technology

The excellent physical properties and antibacterial properties of thermoplastic resin composites are achieved, expanding their application range in specific fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an antibacterial agent, an antibacterial thermoplastic resin composite material and a preparation method thereof.According to the prepared antibacterial agent of the Ag2S / TiO2 / hectorite type, hectorite serves as a carrier, the surface of the antibacterial agent is covered with Ag2S / TiO2, compared with a common antibacterial agent sold in the market, the antibacterial agent has more excellent physical performance and antibacterial performance, and the antibacterial thermoplastic resin composite material can be used for preparing antibacterial materials. The application field of the thermoplastic resin composite material is expanded. The antibacterial agent can generate reactive oxygen species (ROS) with very strong oxidizing ability under ultraviolet irradiation, and the ROS can destroy proteins and lipids of cells, so that the structures and functions of the cells are damaged, including destroying plasma membranes, super-crimped plasmid DNA and internal organelles, and causing significant disorder of cell permeability, so that the cells are prevented from being damaged. The damage of polyunsaturated phospholipids and the structural damage of cell walls finally promote cell death.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to an antibacterial agent, an antibacterial thermoplastic resin composite material and a preparation method thereof. Background Art

[0002] Thermoplastic resin is a widely used polymer resin. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific application fields, very high antibacterial properties of thermoplastic resin are required, which limits the application of thermoplastic resin composites in some specific fields. Summary of the invention

[0003] In view of this, the present invention provides an antibacterial agent, an antibacterial thermoplastic resin composite material and a preparation method thereof to solve the problems raised in the above background technology, have excellent physical properties and antibacterial properties, and expand the application field of thermoplastic resin composite materials.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] The present invention discloses a method for preparing an antibacterial agent, comprising the following steps:

[0006] (1) crushing and sieving the hectorite to obtain hectorite powder;

[0007] (2) mixing the hectorite powder with tetrabutyl titanate, acetone, and deionized water, and reacting at 40-60° C. for 8-12 hours to obtain solution A;

[0008] (3) Solution A, silver ions, thiourea, acetone, and deionized water are mixed, reacted at 50-70° C. for 8-16 hours, filtered, washed, and vacuum dried to obtain an Ag2S / TiO2 / lithium laponite powder antibacterial agent.

[0009] As a further solution of the present invention: in step (1), the mesh size of the hectorite powder is not more than 500.

[0010] As a further solution of the present invention: in step (2), the mass ratio of the hectorite powder, tetrabutyl titanate, acetone and deionized water is (30-40): (16-20): (50-60): (70-110).

[0011] As a further solution of the present invention: in step (3), the mass ratio of solution A, silver phosphate, thiourea, acetone and deionized water is (80-90): (30-40): (28-32): (40-50): (60-70).

[0012] Another aspect of the present invention discloses an antibacterial agent, which is prepared by any of the preparation methods described above.

[0013] The present invention also discloses an antibacterial thermoplastic resin composite material, which is prepared from the following components in parts by weight:

[0014] Thermoplastic resin 80-100 parts,

[0015] 2-4 parts of antibacterial agent,

[0016] Antioxidant 0.1-0.5 parts,

[0017] The antibacterial agent is the Ag2S / TiO2 / lithium soap powder antibacterial agent as described in claim 5.

[0018] As a further solution of the present invention: the thermoplastic resin is at least one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.

[0019] As a further embodiment of the present invention: the antioxidant is at least one of Irganox168, Irganox1010 and Irganox1330.

[0020] The present invention also discloses a method for preparing an antibacterial thermoplastic resin composite material as described in any one of the above, comprising the following steps:

[0021] Weigh the thermoplastic resin, antibacterial agent, and antioxidant according to weight, mix and stir evenly to obtain a mixture;

[0022] The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain an antibacterial thermoplastic resin composite material.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The reaction mechanism of this antibacterial agent is as follows:

[0025] 6CH4N2S+2Ag3PO4→6Ag2S+2(CH4N2)3(PO4)2

[0026] (CH4N2)3(PO4)2+H2O→6NH3+3CO2+2H3PO4

[0027] (C4H9O)4Ti+2H2O→4C4H9OH+TiO2+2H2O

[0028] (2) The present invention synthesizes an antibacterial agent of the Ag2S / TiO2 / hectorite type, which uses hectorite as a carrier and Ag2S / TiO2 covers the surface. Its reaction mechanism is as follows: ① Under ultraviolet light, it can produce highly oxidative reactive oxygen species (ROS). These ROS can destroy the proteins and lipids of cells, thereby causing damage to the structure and function of cells, including damage to the plasma membrane, super-curled plasmid DNA and internal organelles, and cause significant disturbances in cell permeability, damage to polyunsaturated phospholipids and structural damage to the cell wall, ultimately leading to cell death. ② The bacterial cell membrane has a negative charge, and the silver ion Ag + It can firmly adsorb the cell membrane by Coulomb attraction and react with the peptidoglycan of the cell wall, causing the destruction of the inherent components of bacteria or production dysfunction. + Further penetration of the cell wall leads to cell wall rupture, cytoplasm outflow, and ultimately death of the bacteria. The Ag2S / TiO2 / hectorite type antibacterial agent prepared by the present invention has better antibacterial performance than the common antibacterial agents sold on the market. DETAILED DESCRIPTION

[0029] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0031] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0032] PBT (model 2002U), Polyplastics, Japan; PP (model Z30S), Maoming Petrochemical; PE (model 5070), Panjin Ethylene; PA6 (model CM1017), Toray, Japan; PS (model 350), Guoqiao, China Taiwan; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; lanthanum chloride hexahydrate, Shandong Desheng New Materials Co., Ltd.; acetone solution, Hubei Jiufenglong Chemical Co., Ltd.; potassium titanate whisker, Jinan Zi'an Chemical Co., Ltd.; concentrated phosphoric acid, Jining Bocheng Chemical Co., Ltd.; indium acetate, Hubei Chengfeng Chemical Co., Ltd.; sodium bicarbonate, Shandong Runyue Chemical Co., Ltd.; lanthanum nitrate, Shandong Desheng New Materials Co., Ltd.; ammonia water, Jinan Guangyu Chemical Co., Ltd.; chitosan, Qingdao Yuekang Biotechnology Co., Ltd.; sodium hydroxide, Chengdu Zhongzhi Chemical Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF; titanium dioxide, Shandong Zhuo'an Chemical Co., Ltd.; carvacrol, Shandong Shouhua Chemical Co., Ltd.

[0033] The testing instrument used in the present invention is as follows:

[0034] ZSK30 twin-screw extruder, W&P, Germany; JL-1000 tensile testing machine, Guangzhou Guangcai Experimental Instrument Co., Ltd.; HTL900-T-5B injection molding machine, Haitai Plastic Machinery Co., Ltd.; XCJ-500 impact testing machine, Chengde Testing Machine Factory; QT-1196 tensile tester, Dongguan Gaotai Testing Instrument Co., Ltd.; QD-GJS-B12K high-speed mixer, Beijing Hengaode Instrument Co., Ltd.

[0035] All materials are commercially available conventional products.

[0036] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0037] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0038] Preparation Example 1

[0039] (1) The hectorite is crushed in a grinder and passed through a 500-mesh sieve to obtain hectorite powder.

[0040] (2) Weigh 300 g of hectorite powder, 160 g of tetrabutyl titanate, 500 g of acetone, and 700 g of deionized water, add them to a reaction vessel, and react at 40° C. for 8 h to obtain solution A.

[0041] (3) Weigh 800 g of solution A, 300 g of silver phosphate, 280 g of thiourea, 400 g of acetone, and 600 g of deionized water, add them to a reaction vessel, react at 50° C. for 8 h, filter, wash, and place in a vacuum drying oven at 60° C. for 8 h to obtain antibacterial agent M1.

[0042] Example 1

[0043] (1) Weigh 90 parts of PP, 12 parts of antimicrobial agent M1, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0044] (2) The mixed material is placed in a twin-screw extruder for extrusion and granulation to obtain a PP composite material P1.

[0045] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0046] Comparative Example 1

[0047] (1) Weigh 90 parts of PP, 2 parts of commercial antibacterial agent chitosan, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0048] (2) The mixed material is placed in a twin-screw extruder for extrusion and granulation to obtain the PP composite material D1.

[0049] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0050] The PP composite materials prepared in the above Example 1 and Comparative Example 1 were made into test strips by an injection molding machine, and the test data are shown in Table 1 below:

[0051] Table 1

[0052]

[0053] It can be seen from the above table that the antibacterial performance of Example 1 is better than that of Comparative Example 1.

[0054] Preparation Example 2

[0055] (1) The hectorite is crushed in a grinder and passed through a 500-mesh sieve to obtain hectorite powder.

[0056] (2) Weigh 400 g of hectorite powder, 200 g of tetrabutyl titanate, 600 g of acetone, and 1.1 kg of deionized water, add them to a reaction vessel, and react at 60° C. for 12 h to obtain solution A.

[0057] (3) Weigh 900 g of solution A, 400 g of silver phosphate, 320 g of thiourea, 500 g of acetone, and 700 g of deionized water, add them to a reaction vessel, react at 70° C. for 16 h, filter, wash, and place in a vacuum drying oven at 80° C. for 12 h to obtain antibacterial agent M2.

[0058] Example 2

[0059] (1) Weigh 110 parts of PBT, 4 parts of antibacterial agent M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0060] (2) The mixed material is placed in a twin-screw extruder for extrusion and granulation to obtain a PBT composite material P2.

[0061] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0062] Comparative Example 2

[0063] (1) Weigh 110 parts of PBT, 4 parts of commercially available antibacterial agent titanium dioxide, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0064] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.

[0065] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0066] The PBT composite materials prepared in the above Example 2 and Comparative Example 2 were made into test strips by an injection molding machine, and the test data are shown in Table 2 below:

[0067] Table 2

[0068]

[0069] It can be seen from the above table that the antibacterial performance of Example 2 is better than that of Comparative Example 2.

[0070] Preparation Example 3

[0071] (1) The hectorite is crushed in a grinder and passed through a 500-mesh sieve to obtain hectorite powder.

[0072] (2) Weigh 350 g of hectorite powder, 180 g of tetrabutyl titanate, 550 g of acetone, and 900 g of deionized water, add them to a reaction vessel, and react at 50° C. for 10 h to obtain solution A.

[0073] (3) Weigh 850 g of solution A, 350 g of silver phosphate, 300 g of thiourea, 450 g of acetone, and 650 g of deionized water, add them to a reaction vessel, react at 60° C. for 12 h, filter, wash, and place in a vacuum drying oven at 70° C. for 10 h to obtain antibacterial agent M3.

[0074] Example 3

[0075] (1) Weigh 100 parts of PE, 3 parts of antibacterial agent M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;

[0076] (2) The mixed material is placed in a twin-screw extruder for extrusion and granulation to obtain the PE composite material P3.

[0077] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0078] Comparative Example 3

[0079] (1) Weigh 100 parts of PE, 3 parts of commercially available antibacterial agent carvacrol, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;

[0080] (2) The mixed material is placed in a twin-screw extruder for extrusion and granulation to obtain a PE composite material D3.

[0081] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0082] The PE composite materials prepared in the above Example 3 and Comparative Example 3 were made into test strips by an injection molding machine. The test data are shown in Table 3 below:

[0083] Table 3

[0084]

[0085] It can be seen from the above table that the antibacterial performance of Example 3 is better than that of Comparative Example 3.

[0086] Preparation Example 4

[0087] (1) The hectorite is crushed in a grinder and passed through a 500-mesh sieve to obtain hectorite powder.

[0088] (2) Weigh 385 g of hectorite powder, 195 g of tetrabutyl titanate, 555 g of acetone, and 795 g of deionized water, add them to a reaction vessel, and react at 58° C. for 11 h to obtain solution A.

[0089] (3) Weigh 825 g of solution A, 365 g of silver phosphate, 305 g of thiourea, 495 g of acetone, and 695 g of deionized water, add them to a reaction vessel, react at 58° C. for 13 h, filter, wash, and place in a vacuum drying oven at 78° C. for 11 h to obtain antibacterial agent M4.

[0090] Example 4

[0091] (1) Weigh 95 parts of PA6, 3.5 parts of antibacterial agent M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir evenly to obtain a mixture;

[0092] (2) The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a PA6 composite material P4.

[0093] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0094] Comparative Example 4

[0095] (1) Weigh 95 parts of PA6, 3.5 parts of commercially available antibacterial agent carvacrol, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;

[0096] (2) The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a PA6 composite material D4.

[0097] Among them, the twin-screw extruder includes six temperature zones arranged in sequence. The temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 320r / min.

[0098] The PA6 composite materials prepared in the above Example 4 and Comparative Example 4 were made into test strips by an injection molding machine. The test data are shown in Table 4 below:

[0099] Table 4

[0100]

[0101]

[0102] It can be seen from the above table that the antibacterial performance of Example 4 is better than that of Comparative Example 4.

[0103] Preparation Example 5

[0104] (1) The hectorite is crushed in a grinder and passed through a 500-mesh sieve to obtain hectorite powder.

[0105] (2) Weigh 395 g of hectorite powder, 195 g of tetrabutyl titanate, 585 g of acetone, and 1.05 kg of deionized water, add them to a reaction vessel, and react at 48° C. for 11 h to obtain solution A.

[0106] (3) Weigh 888 g of solution A, 375 g of silver phosphate, 309 g of thiourea, 485 g of acetone, and 666 g of deionized water, add them to a reaction vessel, react at 68° C. for 15 h, filter, wash, and place in a vacuum drying oven at 79° C. for 11 h to obtain antibacterial agent M5.

[0107] Example 5

[0108] (1) Weigh 105 parts of PS, 2.5 parts of antibacterial agent M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0109] (2) The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a PS composite material P5.

[0110] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0111] Comparative Example 5

[0112] (1) Weigh 105 parts of PS, 2.5 parts of commercially available antibacterial agent chitosan, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0113] (2) The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a PS composite material D5.

[0114] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0115] The PS composite materials prepared in the above Example 5 and Comparative Example 5 were made into test strips by an injection molding machine. The test data are shown in Table 5 below:

[0116] Table 5

[0117]

[0118] It can be seen from the above table that the antibacterial performance of Example 5 is better than that of Comparative Example 5.

[0119] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0120] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A method for preparing an antibacterial agent, characterized in that: The following steps are involved: (1) crushing and sieving the hectorite to obtain hectorite powder; (2) mixing the hectorite powder with tetrabutyl titanate, acetone, and deionized water, and reacting at 40-60° C. for 8-12 hours to obtain solution A; (3) Solution A, silver ions, thiourea, acetone, and deionized water are mixed, reacted at 50-70° C. for 8-16 hours, filtered, washed, and vacuum dried to obtain an Ag2S / TiO2 / lithium laponite powder antibacterial agent.

2. The preparation method according to claim 1, characterized in that: In step (1), the mesh size of the hectorite powder is not more than 500.

3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the hectorite powder, tetrabutyl titanate, acetone and deionized water is (30-40): (16-20): (50-60): (70-110).

4. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of solution A, silver phosphate, thiourea, acetone and deionized water is (80-90):(30-40):(28-32):(40-50):(60-70).

5. An antibacterial agent, prepared by the preparation method according to any one of claims 1 to 4.

6. An antibacterial thermoplastic resin composite material, characterized in that: It is prepared from the following components in parts by weight: Thermoplastic resin 80-100 parts, 2-4 parts of antibacterial agent, Antioxidant 0.1-0.5 parts, The antibacterial agent is the Ag2S / TiO2 / lithium soap powder antibacterial agent as described in claim 5.

7. The antibacterial thermoplastic resin composite material according to claim 6, characterized in that: The thermoplastic resin is at least one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate, and polyamide 6.

8. The antibacterial thermoplastic resin composite material according to claim 6, characterized in that: The antioxidant is at least one of Irganox168, Irganox1010 and Irganox1330.

9. A method for preparing an antibacterial thermoplastic resin composite material according to any one of claims 6 to 8, characterized in that: The following steps are involved: Weigh the thermoplastic resin, antibacterial agent, and antioxidant according to weight, mix and stir evenly to obtain a mixture; The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain an antibacterial thermoplastic resin composite material.

Citation Information

Patent Citations

  • Antibacterial agent and preparation method thereof

    CN107417966A

  • Preparation method of high-throughput bacteriostatic doped hectorite-metal ion reverse osmosis composite membrane

    CN108854587A

  • Preparation method of antibacterial agent, thermoplastic resin composite material and preparation method of thermoplastic resin composite material

    CN113621181A